2008
DOI: 10.1152/ajpcell.00556.2007
|View full text |Cite
|
Sign up to set email alerts
|

Apical adenosine regulates basolateral Ca2+-activated potassium channels in human airway Calu-3 epithelial cells

Abstract: Apical adenosine regulates basolateral Ca 2ϩ -activated potassium channels in human airway Calu-3 epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 52 publications
(98 reference statements)
0
19
0
Order By: Relevance
“…1). The cyclic nature of the response has been described previously in response to effectors that increase intracellular cAMP (21,35,38). However, it is important to note that this type of response is not uniformly described in publications examining compounds that stimulate ion transport in Calu-3 cells.…”
Section: Methodsmentioning
confidence: 84%
See 1 more Smart Citation
“…1). The cyclic nature of the response has been described previously in response to effectors that increase intracellular cAMP (21,35,38). However, it is important to note that this type of response is not uniformly described in publications examining compounds that stimulate ion transport in Calu-3 cells.…”
Section: Methodsmentioning
confidence: 84%
“…Cells grown to confluent monolayers were used on the 14th-16th day after being seeded onto the Transwells, the time at which the cells show a high-resistance phenotype. As previously reported, there is a batch-to-batch variability in the cells (7,16,38); therefore, in all experimental protocols, control and treated cultures from the same seeding were analyzed in parallel. The average transepithelial resistance for each batch of cells varied between 500 and 700 ⍀/cm 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Cell Culture, Transfection, and Viral Gene Transfers-Human airway epithelial Calu-3 cells were grown as described previously on plastic dishes or permeable supports (24). HEK293T and COS-7 cells were grown in Dulbecco's modified Eagle's medium (Invitrogen) supplemented with 10% fetal bovine serum in a 5% CO 2 , 95% air incubator at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…For short circuit current (I sc ) measurement, the procedures were essentially the same as described previously (24). Calu-3 epithelial monolayers infected with lentiviruses were grown on Snapwells to confluency (air interface culture; resistance Ͼ 800 ohms⅐cm 2 ) and then mounted in Ussing chambers for experiments.…”
Section: Methodsmentioning
confidence: 99%
“…11 It has been further shown that the polarity of a cell monolayer can be changed by ion transport, fluid secretion, and ciliary movement. 12 Abnormality in Ca 2+ homeostasis in the airway epithelium may, therefore, contribute to development of airway hyper-responsiveness and the exacerbation of chronic lung diseases, such as asthma, COPD, silicosis/fibrosis, and lung infections.…”
mentioning
confidence: 99%